CAR-modified anti-CD19 T cells for the treatment of B-cell malignancies: rules of the road. (January 2014) - Gill, Saar; Porter, David L
<x xml:space="preserve">Abstract</x> Introduction: Malignancies of the B lymphocyte or its precursor include B-cell non-Hodgkin lymphoma as well as chronic and acute lymphoid leukemias. These are among the most common hematologic malignancies and many patients with B-cell malignancies are incurable. Although most patients initially respond to first-line treatment, relapse is frequent and is associated with a poor prognosis. T cells that are genetically engineered to express chimeric antigen receptors (CARs) recognizing the B-cell-associated molecule CD19 have emerged as a potentially potent and exciting therapeutic modality in recent years. Areas covered: This review explores the current peer-reviewed publications in the field and a discussion of expert opinion. Expert opinion: Genetic engineering of T cells has become clinically feasible and appears to be safe. Here we provide an insight into the process of patient selection, engineered T-cell production, infusion procedure, expected toxicities and efficacy of this exciting approach as it is practiced in the treatment of B-cell malignancies. Anti-CD19-redirected T cells likely represent the vanguard of an exciting new approach to treating cancer.